The Impact Of Human Capital Quality, Public Health, Education Quality, And Public Services On Governance, All Of Which Have Implications For Community Well-Being - Siregar, Budi Alamsyah; Suma, Dewi; Ichsan, Reza Nurul (Moneter: Jurnal Keuangan dan Perbankan, 2023)
The objective of this study was to assess the impact of human resource quality, public health, education quality, and public services on governance, which has an impact on community welfare. A random sampling approach was used to randomly select 330 respondents. Questionnaires were used to collect data. SEM-PLS with structural equation modelling (SEM) was used for data analysis. Based on the findings of the study, the quality of human resources, public health, quality of education, public services, and governance all have a significant impact on community welfare. These five research variables are prioritised for improvement. The quality of human resources, public health, education, and public services show useful results, which can be a solution to welfare problems to achieve good governance, as long as they are within the framework of improving community welfare and not exploiting them for other personal gains. This research also shows the importance of the Muara Enim Regency government in preventing corrupt practices, especially since corrupt practices have a significant impact on people's welfare, because they not only make administrative procedures slow, expensive, and inefficient, but also divert resources to local governments. The Muara Enim Regency Government is expected to be able to equip its people with quality human resources, health services, public education, and public services, resulting in superior governance. This research also proposes that the Muara Enim Regency Government be more successful in making policies to stay on track and improve the human development index.